Bread staling - Chinachoti, Pavinee (CRC Press LLC, 2011)
The role of starch, gluten, lipids, water, and other components in bread staling is a subject of continual study using advanced analytical methodologies and sophisticated multidisciplinary approaches. Significant recent progress has been made in the fundamental understanding of the events leading to bread staling.